2013
DOI: 10.1002/2013jd019964
|View full text |Cite
|
Sign up to set email alerts
|

Similarity and difference of the two successive V6 and V7 TRMM multisatellite precipitation analysis performance over China

Abstract: [1] Similarities and differences of spatial error structures of surface precipitation estimated with successive version 6 (V6) and version 7 (V7) Tropical Rainfall Measuring Mission (TRMM) Multisatellite Precipitation Analysis (TMPA) algorithms are systematically analyzed through comparison with the China Meteorological Administration's national daily precipitation analysis from June 2008 to May 2011. The TMPA products include V6 and V7 real-time products 3B42RTV6 and 3B42RTV7 and research products 3B42V6 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
154
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(174 citation statements)
references
References 46 publications
16
154
0
1
Order By: Relevance
“…However, Chen et al (2013a) found the false alarm ratios of TRMM3B42 and TRMM3B42RT to increase with an increase in rainfall intensity. The differences are attributed mainly to observed data.…”
Section: Contingency Statisticsmentioning
confidence: 86%
See 3 more Smart Citations
“…However, Chen et al (2013a) found the false alarm ratios of TRMM3B42 and TRMM3B42RT to increase with an increase in rainfall intensity. The differences are attributed mainly to observed data.…”
Section: Contingency Statisticsmentioning
confidence: 86%
“…Several studies have been carried out to analyse the uncertainty of TRMM in high-latitude regions (Yong et al, 2010(Yong et al, , 2014Chen et al, 2013a;Zhao and Yatagai, 2014), but studies in northeast China are few. Evaluation of GLDAS data has generally been limited to the United States and other observationrich regions of the world (Kato et al, 2007); assessments and applications in other regions are rare (Wang et al, 2011;Zhou et al, 2013).…”
Section: W Qi Et Al: Evaluation Of Global Fine-resolution Precipitamentioning
confidence: 99%
See 2 more Smart Citations
“…The current operational Version-7 TMPA system produces two standard user-level (Level 3) rainfall products at relatively fine resolution (0.25˝ˆ0.25˝, 3 h), i.e., the real-time 3B42RT (hereafter referred to as "RTV7"; 6-9 h after observation time) for the latitude band 60˝N-60˝S and the gauge-adjusted, post-real-time 3B42V7 for research purposes (hereafter "V7"; two months latency) with spatial coverage of 50˝N-50˝S [5,6]. Recently, these two quasi-global satellite precipitation products have been widely utilized in various hydrological and meteorological applications in China [7][8][9][10][11][12][13]. Over the years, there have been many efforts to compare and validate available satellite precipitation estimates at global, regional, or basin scales [9,10,[14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%